NANOPARTICLES FROM ONION (ALLIUM CEPA.L) EXTRACT SUPPRESS BCL-2 EXPRESSION IN MCF-7 CELLS IN VITRO - Jayanti S.; Suseno D.N.; Suseno D.A.N. (Russian Journal of Agricultural and Socio-Economic Sciences, 2019)
This research aimed to make nanoparticles from Allium cepa. L extract that can inhibit Bcl-2 protein expression in MCF-7 cells in vitro. The particles were broken down to nano with the addition of NaTPP dissolved in distilled water and chitosan dissolved in 1% acetic acid. The particle size based on the SEM and PSA tests had an average size of 336 nm. Nanoparticles from Allium cepa. L extract based on the KLT test contained flavonoids, saponins, and tannins. MCF-7 cells were treated with doses of 40 μg/ml, 80 ug/ml, 160 ug/ml, and 320 ug/ml. The results showed that nanoparticles from Allium cepa. L extract had cytotoxicity in MCF-7 cells with the IC50 value of 235 μg/ml and proved to inhibit Bcl-2 protein expression.